Oncovascular Surgery and the Making of the Oncovascular Surgeon - Sallam, Kareem (Vasc Specialist Int, 2019)
Patients diagnosed with tumors that are located in vicinity of the major axial vessels are inconsistently managed because they are often considered unresectable. The management of these patients remains at the periphery of various established sub-specialties that are prevalent under the current medical specialty. These patients are required to be treated by an oncovascular surgeon. This article discusses some key points in understanding the reasons for establishing a specialty branch, oncovascular surgery, to treat complex tumors with vessel invasion. This article also reviews important issues about leadership and how to train and educate oncovascular surgeons.